Optimal Routing Between Clusters Based on Circular Search Method in WSN - Xiang Yu; Lei Liu; Kun Wu (Dianxin kexue)
In order to solve the problem of the nodes' energy consumption balance caused by single hop routing algorithm in LEACH protocol. By calculation and analysis of the optimal number of hops of inter cluster multi-hops, the cluster head node got an ideal path to the base station. A ring search method was proposed to find the optimal path close to the ideal path. Then, a multi-hops routing algorithm from the cluster head to the base station was obtained. The experimental results show that the performance of the multi-hops routing algorithm from the cluster head to the base station compared with LEACH protocol is higher in the balance of nodes' energy consumption and prolong the network lifetime.